Australian TV news : new forms, functions, and futures - Harrington, Stephen (Intellect, 2013)
Drawing extensively on qualitative audience research and industry interviews, this book demonstrates that while 'infotainment' and satirical programmes may not follow the journalism orthodoxy, they nevertheless play an important role in the way everyday Australians understand what is happening in the world.